AuICl-bound N-heterocyclic carbene ligands form MII4(LAuCl)6 integrally gilded cages. Issue 12 (5th October 2015) - Ramsay, William J.; Foster, Jonathan A.; Moore, Katharine L.; Ronson, Tanya K.; Mirgalet, Raphaël J.; Jefferson, David A.; Nitschke, Jonathan R.
Abstract : A gold(i ) N -heterocyclic carbene (NHC) ligand self-assembles with zinc(ii ) and cadmium(ii ) templates into bimetallic MII4L6 cage frameworks. Abstract : The incorporation of an N -heterocyclic carbene (NHC) moiety into a self-assembled MII4L6 cage framework required the NHC first to be metallated with gold(i ). Bimetallic cages could then be constructed using zinc(ii ) and cadmium(ii ) templates, showing weak luminescence. The cages were destroyed by the addition of further gold(i ) in the form of Au I (2, 4, 6-trimethoxybenzonitrile)2 SbF6, which caused the reversibly-formed cages to disassemble and controllably release the Au I -NHC subcomponent into solution. This release in turn induced the growth of gold nanoparticles. The rate of dianiline release could be tuned by capsule design or through the addition of chemical stimuli, with different release profiles giving rise to different nanoparticle morphologies.